Sea surface temperature reconstruction based on dinoflagellates from the North Atlantic - Lucy Edwards; Peta J Mudie; Anne de Vernal (PANGAEA, 1991)
The application of quantitative and semiquantitative methods to assemblage data from dinoflagellate cysts shows potential for interpreting past environments, both in terms of paleotemperature estimates and in recognizing water masses and circulation patterns. Estimates of winter sea-surface temperature (WSST) were produced by using the Impagidinium Index (II) method, and by applying a winter-temperature transfer function (TFw). Estimates of summer sea-surface temperature (SSST) were produced by using a summer-temperature transfer function (TFs), two methods based on a temperature-distribution chart (ACT and ACTpo), and a method based on the ratio of gonyaulacoid:protoperidinioid specimens (G:P). WSST estimates from the II and TFw methods are in close agreement except where Impagidinium species are sparse. SSST estimates from TFs are more variable. The value of the G:P ratio for the Pliocene data in this paper is limited by the apparent sparsity of protoperidinioids, which results in monotonous SSST estimates of 14-26°C. The ACT methods show two biases for the Pliocene data set: taxonomic substitution may force extquotesinglematches extquotesingle yielding incorrect temperature estimates, and the method is highly sensitive to the end-points of species distributions. Dinocyst assemblage data were applied to reconstruct Pliocene sea-surface temperatures between 3.5-2.5 Ma from DSDP Hole 552A, and ODP Holes 646B and 642B, which are presently located beneath cold and cool-temperate waters north of 56°N. Our initial results suggest that at 3.0 Ma, WSSTs were a few degrees C warmer than the present and that there was a somewhat reduced north-south temperature gradient. For all three sites, it is likely that SSSTs were also warmer, but by an unknown, perhaps large, amount. Past oceanic circulation in the North Atlantic was probably different from the present.
Supplement to: Edwards, L et al. (1991): Pliocene paleoclimatic reconstruction using dinoflagellate cysrs: comparison of methods. Quaternary Science Reviews, 10(2-3), 259-274, https://doi.org/10.1016/0277-3791(91)90024-O